(untitled) (Nóema, 2013)
In this paper we describe the theory of subjectivity elaborated by Enzo Paci through his study of Husserl’s phenomenology. The investigation of the subject’s pre-categorial dimension brings the author to develop a concept of subjectivity as infinite aim (telos). This topic can be put in the wider context of a rethinking of philosophy as practice of transformation of reality.